Anti-cancer activity of Chaga mushroom (Inonotus obliquus) against dog bladder cancer organoids - Abugomaa, Amira; Elbadawy, Mohamed; Ishihara, Yusuke; Yamamoto, Haru; Kaneda, Masahiro; Yamawaki, Hideyuki; Shinohara, Yuta; Usui, Tatsuya; Sasaki, Kazuaki (Frontiers in Pharmacology, 2023)
Despite its disadvantages, chemotherapy is still commonly used for the treatment of bladder cancer (BC). Developing natural supplements that can target cancer stem cells (CSCs) which cause drug resistance and distant metastasis is necessary. Chaga mushrooms are popular to have several health-promoting and anti-cancer potentials. Organoid culture can recapitulate tumor heterogeneity, epithelial environment, and genetic and molecular imprints of the original tissues. In the previous study, we generated dog bladder cancer organoids (DBCO) as a novel experimental model of muscle-invasive BCO. Therefore, present study aimed to examine the anti-tumor potentials of Chaga mushroom extract (Chaga) against DBCO. Four strains of DBCO were used in the present study. Treatment with Chaga inhibited the cell viability of DBCO in a concentration-dependent way. Treatment of DBCO with Chaga has significantly arrested its cell cycle and induced apoptosis. Expression of bladder CSC markers, CD44, C-MYC, SOX2, and YAP1, declined in the Chaga-treated DBCO. Also, Chaga inhibited the phosphorylation of ERK in DBCO. Expression of downstream signals of ERK, C-MYC, and Cyclins (Cyclin-A2, Cyclin-D1, Cyclin-E1, and CDK4) was also inhibited by Chaga in DBCO. Interestingly, the combinational treatment of DBCO with Chaga and anti-cancer drugs, vinblastine, mitoxantrone, or carboplatin, showed a potentiating activity. In vivo, Chaga administration decreased tumor growth and weight of DBCO-derived xenograft in mice with the induction of necrotic lesions. In conclusion, Chaga diminished the cell viability of DBCO by inhibiting proliferation-related signals and stemness conditions as well as by arresting the cell cycle. Collectively, these data suggest the value of Chaga as a promising natural supplement that could potentiate the effect of adjuvant chemotherapy, lower its adverse effects, and thus, limit the recurrence and metastasis of BC.